Analisis Tingkat Kepuasan Konsumen Bibit Alpukat Cipedak Terhadap Kinerja Pelaksanaan Bauran Pemasaran di Kelompok Tani Sejahtera Makmur Jakarta Selatan - Zahra, Annisa (Department of Agribusiness, Faculty of Science and Technology, UIN Syarif Hidayatullah Jakarta, 2025)
ABSTRACTThis research aims to: (1) Analyze the characteristics of Cipedak avocado seed consumers; (2) Analyzing the level of consumer satisfaction of Cipedak avocado seeds on the performance of marketing mix implementation; (3) Analyzing differences in satisfaction based on consumer characteristics; and (4) Formulate attributes that are priority improvements in Sejahtera Makmur Farmers Group, South Jakarta. Data types and sources use qualitative data and quantitative data, with data collection methods in the form of interviews, observations, literature studies and questionnaires. Data analysis uses the Chi Square method, descriptive analysis, CSI, and IPA. The research results show that 1) The majority of consumers live in South Jakarta, male, age range 45-54 years, have at least a high school/vocational education, married status, farmer profession, income IDR 4,000,000-7,000,000/month; 2) Satisfaction level of 87.03%, which means consumers are